Integrating Islamic Ethics into AI Literacy Curriculum in Muhammadiyah Educational Institutions: A Conceptual Model - Hikmatunnajat, Mukhammad; Muthoifin, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The development of artificial intelligence (AI) technology in education presents ethical challenges that require attention, especially in the context of Islamic education. This study aims to formulate a model of AI literacy curriculum that integrates Islamic ethics, based on the principles of maqāṣid al-sharl'ah, tawhid, and akhlak. Using a descriptive-conceptual qualitative approach, this study shows that AI literacy in Muhammadiyah educational institutions should go beyond mere technical skills, but also include the development of moral character aligned with Islamic values. The proposed curriculum model aims to build critical awareness, digital etiquette, and social responsibility among students in using technology. The study also suggests gradual implementation at the primary and secondary education levels, with the hope of creating a generation that is not only skilled in technology but also moral and ethical. The findings of this study are expected to serve as a reference for developing an ethical technology-based education curriculum in Muhammadiyah institutions and Islamic education in general.